CULTURAL LITERACY ANALYSIS OF PGSD STUDENTS IN TANAH AIR NUSANTARA STUDENT EXCHANGE PROGRAM - Hana Sakura Putu Arga; Siti Ruqoyyah; Medita Ayu Wulandari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine PGSD students' cultural literacy abilities to adapt to the diversity of the nation, including how to behave, how to communicate, and how to interact between one and another through an Indonesian student exchange program. In this program students from several universities were united in an online learning process and it was hoped that through this program every student had the ability to understand various ethnic groups, languages, beliefs, habits, customs, and social strata as a national identity. This study utilized a descriptive method with the research subjects of PGSD students in